The importance of leadership training for women leader and the leadership IQ profiles of women leaders in yogyakarta Special Province - Aliyah Rasyid Baswedan (JOURNAL OF EDUCATION, 2010)
This research aims at revealing how the women leadership profiles in Yogyakarta Special Province, including their ability to select their own team, the ability to cooperate, the ability to solve the problem, encouraging the enthusiasm of working, to maintain positive working culture and do synergy, which all of them figure someones leadership IQ. This research is a survey research of women leaders who have joined to an association namely Badan Kerjasama Organisasi Wanita Propinsi Daerah Istimewa Yogyakarta (BKOW-Yogyakarta Special Province). Then the researcher took the sample randomly to the 35 people. They answered questionnaire, which refers to Murphy measurer, which has been tested and proven reliable. The collected data was analyzed using percentage, descriptive analysis and cross tabulation. The research shows that the ability as an elector to cooperate, to solve conflict, to encourage enthusiasm of working, to maintain positive culture of working, and do synergy is in the average. The research shows that 20% of respondents have high leadership IQ, 45.7%, have average leadership IQ and 34. 3% have low leadership IQ. It means that 65% the leadership IQ of women respondents in this research is in a high and average rate. Meanwhile, the low rate is 35%. This fact leads us to intensively pay attention upon the ability of women leadership by conducting an intensive and comprehensive training. Research shows that the leadership IQ of women is relatively mediocre. Therefore leadership training for women will be highly beneficial for them considering the roles they play